Inferiorly Pedicled Nasolabial Flap for Reconstruction of Anterior Maxilla Defects Class I and II. Issue 2 (March 2018) - Chen, Qingli; Abasi, Keremu; Gong, Zhongcheng; Ling, Bin; Liu, Hui; Shao, Bo
Abstract : Objectives: The aim of this study was to present the use of inferiorly pedicled nasolabial flap (IPNF) in the reconstruction of anterior maxilla defects class I and II. Methods: Seven patients, 4 females and 3 males, aging from 38 to 75 (mean = 55.9) years old, from 2014 to 2017 reconstructed anterior part of maxilla with or without oronasal communication were included in this study. Five patients diagnosed with squamous cell carcinoma, 1 patient presented with epithelial-myoepithelial carcinoma, and 1 patient had ameloblastoma. The IPNFs were harvested in 7 patients. Follow-up data were collected for a period ranging from 9 to 26 months. Speech, mastication, and aesthetic outcomes were evaluated with a questionnaire in interview. Results: All patients healed without infection, flap loss, and flap failure. Five patients without prothetic treatment had little pronunciation problem (score: 1 to 3 points), while 2 patients with removable partial denture had excellent speech clarity (score: 1 to 2 points). All patients had no problem with mastication (score: 1 to 2 points). Aesthetic outcomes were acceptable in all patients (score: 1 to 3 points). Conclusion: The IPNF is a good option for reconstruction of anterior maxilla defects class I and II.